Tetracanthella doftana sp. nov. (Collembola, Isotomidae) from Romania, with a key to Carpathian Tetracanthella Schött, 1891 - Fiera, Cristina; Konikiewicz, Marta; Skarżyński, Dariusz (Zootaxa, 2013)
A new species of the Tetracanthella pilosa group is described from Romanian Carpathians. T. doftana sp. nov. is similar to T. andalusiaca Deharveng, 1987. They differ by the number of sublobal hairs, size of macrochaetae and distribution. A key to Carpathian Tetracanthella Schött, 1891 species is also given.